COGNITIVE LOAD THEORY'S COHERENCE PRINCIPLE: THEORY MEETS REALITY - Arts, Julie M. (My University, 2009)
For learning to occur, the individual must make sense of the presented material by attending to relevant information, mentally reorganizing it, and connecting it with existing knowledge. A great deal of this process occurs in working memory. However, working memory is extremely limited. With the learning process in mind, the challenge is evident. The learner must actively process new material within the limits of working memory. Cognitive load theorists determine how to best design instruction with this limitation in mind. Cognitive load theory suggests that instruction imposes three different types of cognitive load, and because the total mental capacity is limited, it is important to balance all three forms. When a lesson is high in one type of cognitive load, there is very little capacity remaining for the other forms. To create instruction that meets these goals, cognitive load theorists have developed several universal principles that are proven to result in efficient instructional environments by accommodating the limits and exploiting the strengths of working memory. This paper looks closely at the coherence principle. Based on the coherence principle, instruction should not include extraneous material (i.e., learning material that is not directly related to the lesson's objectives). Extraneous materials can provide interest, expand on key ideas, or provide technical background. Regardless of the purpose, extraneous material imposes undue cognitive load on the learner. Therefore, learning material should not be included unless it is essential to the learning goals. Knowing that theories often conflict with real-world constraints or expectations, this paper looks for ways that instruction can foster learning with these cognitive principles in mind even when they cannot be leveraged in their full sense. The instructional designer may attempt to minimize extraneous material. However, the intent is moot if the client (for whom the instruction is created) does not share the same intent. So while extraneous material should be ruthlessly weeded out, the instructional designer needs a backup plan. The purpose of this paper is to develop a method by which the framework behind the cognitive load theory and its principles can be leveraged to reduce the effects of extraneous material. While the cognitive load theory and its principles pertain to both paper and electronic learning materials, the backup plan developed in this paper requires the use of electronic learning formats.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Arts-English
Keywords: Human information processing; Cognition; Learning ability; Instructional systems designs